Carbon footprint valuation of Bangladesh transportation under environmental regulations - Dongsheng Li; Muhammad Yousaf Raza; Guangwei Zhang (Energy Strategy Reviews)
The study detects and analyzes the driving factors underlying the CO2 emission variations in the transport sector of Bangladesh, including the carbon coefficient, fossil fuel ratio, energy use per unit turnover, turnover per unit of transport value-added, and value-added of transport from 2003 to 2021. The objective is to analyze the transportation (i.e., land, water and air) factor's effects under the logarithmic mean Divisia index, Tapio index, CO2 mitigation potential methods, and their decouplings. The results show that: (i) value-added was the main CO2 driving factor, while CO2 coefficient, fuel substitution, energy use, and turnover value mitigated CO2 emissions. (ii) Land and water transport seemed to be the main CO2 producers and meaningfully contributed to the economy. (iii) Only two decoupling states─weak decoupling and strong decoupling appeared, in which economic growth was the significant turn towards the best state. (iv) Sub-transportation presented significant and strong decouplings in the maximum intervals. (iv) The carbon mitigation rate was observed at 0.26 % during the period in which the economic structural factor was the main factor contributing to declining CO2 emissions. Finally, the study proposes frameworks that will support policymakers in estimating energy and technological policies for climate and economic sustainability.